Analisis Kelayakan Finansial Usaha Penyulingan Minyak Nilam Di Desa Tompasobaru Dua Kecamatan Tompasobaru Kabupaten Minahasa Selatan - Tadinting, Syelin Olysia; Katiandagho, Theodora Maulina; Baroleh, Jenny (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
Patchouli oil is an essential oil obtained by distillation which will produce oil. This study aims to analyze the financial feasibility of patchouli oil refining business in Tompasobaru Dua Village, Tompasobaru District, South Minahasa Regency. This research was conducted from April 2023 to June 2023. Data collection techniques were through direct interviews with business owners. The data analysis used is the criterion of investment feasibility analysis by calculating Net present value (NPV), Internal rate of return (IRR), Net benefit cost ratio (Net B/C Ratio), Payback period (PP). From the results of the research conducted, it can be concluded that the patchouli oil refinery business in Tompasobaru Dua Village, Tompasobaru District, South Minahasa Regency is financially profitable and feasible to run. This patchouli oil refining business has met the business feasibility criteria based on the Net Present Value (NPV) which has a positive value of Rp.34,462,573, the Internal Rate of Return (IRR) value is greater than the interest rate which is 8.42%, the Net Benefit Cost value The ratio (Net B/C) of 1.381814461 is greater than 1 and the Payback Period (PP) value is very short compared to the maximum payback period which is 2 months.